2017
DOI: 10.7860/jcdr/2017/22515.9266
|View full text |Cite
|
Sign up to set email alerts
|

Occlusal Traits of Primary Dentition among Pre-School Children of Mehsana District, North Gujarat, India

Abstract: Introduction: Aesthetic and functional problems in the dentofacial complex among children are often attributed to the disturbances in the dentofacial growth and development. This can be recognized during routine dental visits. This study pursued to assess the occlusion of the primary dentition in three to five-year-old children. Aim:To study the occlusal traits of the primary dentition in a group of three to five-year-old North Gujarat children of Mehsana district and the variation in their occlusion relative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 18 publications
(3 reference statements)
3
8
0
1
Order By: Relevance
“…8 Similar finding was also noted in several studies. [11][12][13][14][15][16][17] Considering canine relation, class I canine relationship was present in (83.0% for left canines, and 84.0% for right canines), followed by class II (11.0% for left canines, and 9.0% for right canines) and class III (7.0% for left canines, and 6% for right canines). One of the study done in Wardha District of India, had also concluded that among the canine relation, Class I (47.2%) showed highest value followed by Class II (42.8%) and Class III (9.9%).…”
Section: Discussionmentioning
confidence: 99%
“…8 Similar finding was also noted in several studies. [11][12][13][14][15][16][17] Considering canine relation, class I canine relationship was present in (83.0% for left canines, and 84.0% for right canines), followed by class II (11.0% for left canines, and 9.0% for right canines) and class III (7.0% for left canines, and 6% for right canines). One of the study done in Wardha District of India, had also concluded that among the canine relation, Class I (47.2%) showed highest value followed by Class II (42.8%) and Class III (9.9%).…”
Section: Discussionmentioning
confidence: 99%
“…The result is in concurrence with other similar studies. [ 5 7 8 9 10 11 12 13 14 15 ] However, some of other studies have also shown increased mesial step prevalence. [ 1 16 17 18 19 ] Flush terminal plane relationship has been found to decrease at the age of 5 years,[ 20 ] but this was not observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Less than ten percent children had distal step relationship and asymmetric molar relationship. Out of the seven studies [67][68][69][70][71][72][73] included in this category, only one study had provided gender wise data. The authors of this study reported that males had significant to highly significant higher prevalence for all the three molar relationships compared to females [70].…”
Section: Terminal Plane Relationship Of Second Primary Molarsmentioning
confidence: 99%